Outcomes Among Patients with Breakthrough SARS-CoV-2 Infection After Vaccination. (September 2021) - Butt, Adeel A.; Nafady-Hego, Hanaa; Chemaitelly, Hiam; Abou-Samra, Abdul-Badi; Khal, Abdullatif Al; Coyle, Peter V.; Kanaani, Zeina Al; Kaleeckal, Anvar H.; Latif, Ali Nizar; Masalmani, Yousuf Al; Bertollini, Roberto; Raddad, Laith J. Abu
Highlights: Severe disease was recorded in 10% of persons with breakthrough infections In comparison, 26% of unvaccinated controls with infection had severe disease Older age was a risk factor for severe disease in those with breakthrough infection Vaccination status was associated with a significantly lower risk of severe disease Abstract: Background: Breakthrough infections after SARS-CoV-2 vaccination have been reported. Clinical outcomes in these persons are not widely known. Methods: We evaluated all vaccinated persons with breakthrough infection ≥14 days after the second vaccine dose and unvaccinated controls matched on age, sex, nationality, and reason for testing between December 23, 2020 and March 28, 2021 in Qatar. Our primary outcome was severe disease defined as hospitalization, mechanical ventilation, or death. Results: Among 456 persons cases of breakthrough infection and 456 unvaccinated matched controls with confirmed infection, median age was 45 years, 60.7% were males, and ≥1 comorbid condition was present in 61.2% of the vaccinated and 47.8% of the unvaccinated persons (P=0.009). Severe disease was recorded in 48 (10.5%) of the vaccinated and 121 (26.5%) of the unvaccinated group (P<0.001). Factors associated with severe disease included increasing age (HR vs. <40 years old: >40–60 years, HR 2.32; >60–70 years, HR 4.34; >70 years, HR 5.43); presence of symptoms at baseline (HR 2.42, 95%CI 1.44-4.07); and being unvaccinated (HR 2.84, 95%CI 1.80-4.47). Conclusions: In persons with breakthrough SARS-CoV-2 infection, increasing age is associated with a higher risk of severe disease or death, while vaccination is associated with a lower risk. Presence of comorbidities was not associated with severe disease or death among persons with breakthrough infection.